POTENSI PENGHEMATAN ENERGI LISTRIK DI INDUSTRI KARPET - Hasan, Achmad (Jurnal Energi dan Lingkungan (Enerlink), 2009)
Potential energy savings is one way to plan for optimizing the supply and use ofenergy needed by the industry. Portrait of the use of electrical energy used incarpet industry supplied from PT.PLN (Persero) with the power contract for 1730kVA through 2 pieces of the transformer with electrical energy consumption by anaverage of 19,979,941 kWh per year. Supplies of gas / diesel fuel oil for boilerfeed of 1.4537 million m3 per year with a calorific value of 6 tons / hour and 900liters of diesel oil per year. Working voltage is still in the allowed range, while forthe voltage unbalance is still low at under 2.5% and total harmonic distortionvoltage is still low at 2% and this can be expressed less well and there are lowpower factor at some expense. In case: PT.Classic Prima Carpet Industries.Kata kunci: energi, listrik, penghematan, filter harmonik, konversi, konservasi